2008
DOI: 10.1523/jneurosci.5031-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Neural Oscillatory Activity to Speech Sounds in Schizophrenia: A Magnetoencephalography Study

Abstract: Schizophrenia impairs many cognitive functions, and abnormalities in language processing have been proposed as one of the bases for this disorder. Previously, it was reported that different magnetoencephalography (MEG) patterns of the evoked oscillatory activity (eOA) of 20 -45 Hz to speech and nonspeech sounds were evidence of a fast mechanism for the representation and identification of speech sounds in humans. The current study tested the hypothesis that the schizophrenics would show abnormal neural oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 24 publications
3
53
0
Order By: Relevance
“…Like most (Krishnan, Hetrick, 2009, Light, Hsu, 2006, Spencer, Niznikiewicz, 2009, Spencer, Salisbury, 2008, Teale, Collins, 2008), but not all (Hamm, Gilmore, 2011), prior reports, we found a reduction in the PLF, or phase consistency across trials, of the 40 Hz ASSR in SZ patients. We also found reduced auditory GBR PLF, consistent with our prior report (Roach and Mathalon, 2008) from a patient sample that partially overlapped with the current sample, and replicating some (Hall, Taylor, 2009, Hirano, Hirano, 2008, Leicht, Kirsch, 2010), but not all (Krishnan, Hetrick, 2009, Spencer et al, 2007, Teale, Collins, 2008), prior studies. Further, reduced total power in SZ relative to HC in both the 40 Hz ASSR and GBR measures replicates the findings of Krishnan et al (Krishnan, Hetrick, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Like most (Krishnan, Hetrick, 2009, Light, Hsu, 2006, Spencer, Niznikiewicz, 2009, Spencer, Salisbury, 2008, Teale, Collins, 2008), but not all (Hamm, Gilmore, 2011), prior reports, we found a reduction in the PLF, or phase consistency across trials, of the 40 Hz ASSR in SZ patients. We also found reduced auditory GBR PLF, consistent with our prior report (Roach and Mathalon, 2008) from a patient sample that partially overlapped with the current sample, and replicating some (Hall, Taylor, 2009, Hirano, Hirano, 2008, Leicht, Kirsch, 2010), but not all (Krishnan, Hetrick, 2009, Spencer et al, 2007, Teale, Collins, 2008), prior studies. Further, reduced total power in SZ relative to HC in both the 40 Hz ASSR and GBR measures replicates the findings of Krishnan et al (Krishnan, Hetrick, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…However, we are unaware of any study that directly correlated the two measures. In addition, despite multiple reports of abnormal GBR (Hall et al, 2011, Hall et al, 2009, Hirano et al, 2008, Leicht et al, 2010, Lenz et al, 2010, Roach and Mathalon, 2008, Teale et al, 2008) and 40 Hz ASSR (Brenner et al, 2003, Hamm et al, 2011, Krishnan et al, 2009, Kwon et al, 1999, Light et al, 2006, Spencer et al, 2009, Spencer et al, 2008, Teale, Collins, 2008, Vierling-Claassen et al, 2008, Wilson et al, 2008) in schizophrenia, no study has examined the relationship between these measures in the same patient sample to determine if they reflect distinct pathophysiological processes. Accordingly, the present study examines the relationship between GBR and ASSR in healthy controls and patients with schizophrenia, and further compares the relative sensitivity of these measures to the pathophysiology underlying deficient gamma oscillations in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a similar pattern has been reported in previous task-related studies of gamma-band oscillations: Although both the stimulus-locking of local gamma-band phase 19,31,32 and the long-range synchrony of gamma oscillations 16 are reduced in patients with schizophrenia, their correlation with positive symptoms is a positive one. In contrast, a study that reported an increased delayed left-hemisphere gamma-band response to speech in patients with schizophrenia 13 found a negative correlation with hallucination severity. All the above findings indicate that increased psychopathology is associated with more "normal" measures of local phase-coupling and/or interregional synchronization in the gamma frequency range.…”
Section: Discussionmentioning
confidence: 68%
“…36 Reductions in gamma-band amplitude have been demonstrated for a wide range of cognitive and perceptual paradigms, including working memory, 37 executive control, 38 and perceptual processing. 39,40 There is preliminary evidence that the decrease in gamma-band spectral power is independent of medication status. 38 …”
Section: High-frequency Oscillations In Schizophreniamentioning
confidence: 99%